A Review on Halal Food Research - Aam; Dwi (SMART Insight, 2021)
Halal can be defined as a quality standard that complies with Islamic law and is used in every activity carried out by Muslims. Muslims choose halal products and services as a form of obedience to Islamic Sharia law. The quality of halal products, commonly known as Halalan Thoyyiban, is why Muslims and non-Muslims use halal products because there is a guarantee of cleanliness, safety, and product quality for the entire production chain. The State of The Global Islamic Economic 2016/2017 report shows that the halal industry is experiencing rapid development in halal food sectors. This study aims to determine the development of halal food research trends published by leading journals on Islamic financial economics. The data analyzed consisted of 1004 indexed research publications. The data is then processed and analyzed using the VoS viewer application to find out the bibliometric map of the development of halal food research. The results show that since 1990 there has been an increase in the number of published articles on halal food and Rohman A., who writes the most about halal food. The institution that publishes the most papers related to halal food is the Faculty of Business and Accountancy, University of Malaya, Kuala Lumpur, Malaysia. In contrast, the country that publishes the most papers related to the halal food theme is Malaysia.